Effect of osmotic agent supplementation in the diet of buffalo on some rumen functions and blood electrolytes - PURI, J P; GARG, S K (The Indian Journal of Animal Sciences, 2014)
Osmotic active agents like sodium bicarbc,nate and sodium chloride increase the dilution rate/outflow rate which improves the animal performance. Keeping this in view, the present studies were conducted on 4 rumen fistulated buffaloes (2 to 2Â½, years). They were fed wheat straw+concentrate mixture as per requirements, group A. Sodium chloride was added @ 50 g and 100 g/head daily in groups Band C, respectively, for I month. The feed intake was not affected in group B but it reduced significantly in group C. Animals consumed more water in both the treatment groups, perhaps to maintain the water electrolyte balance. Rumen water kinetics studies also showed an increase in the outflow rate and rumen volume in group C only where sodium chloride was supplemented @ 100 glhead daily. Total population of bacteria and protozoa were not affected in group B, but their number reduced significantly in group C, which might be due to increase in flow rate in this group. Further the holotrichs protozoa were affected more than the entodeniomorphs. These results showed that 50 g sodium chloride/head daily is optimum level for better feed utilization in buffalo.